Office employees satisfaction towards workplace utilities : a case study in UiTM Terengganu / Wan Zuhaila Wan Abd. Rahman, Norrini Muhammad and Jefry Elias - Wan Abd. Rahman, Wan Zuhaila; Muhammad, Norrini; Elias, Jefry (2011)
Office building is important for all types of organization. It is a place to accommodate information and process knowledge (filing, planning, designing, supervising, analyzing, deciding, and communicating). “Utilities” need to always be in good condition and satisfy the employees as they are valuable assets to the organization. In addition, organization might face problems, reduced productivity, higher employees’ turnover, increased absenteeism, and health care cost caused by job stress. The word “utility” is used in this research to indicate “usefulness or a potential capacity to provide a service”. In many public sector organizations, this responsibility lies in facility managers, who are concerned with workplace issues that immediately affect building occupants. The study will be focused on the office employees in UiTM Terengganu, who have their own workstation but in shared office. However, this study will be focused only on employees who work in the office building and is limited to office employees in grade N17 and above who have been working for at least 3 months as they are accustomed with all of the facilities provided. The objectives of this research are to identify the most important factor contributing toward office employees satisfaction in UiTM Terengganu, to measure office employees satisfaction with overall workplace utilities provided by UiTM Terengganu, to investigate the relationship between workplace utilities and employees’ satisfaction in UiTM Terengganu, and to provide recommendations on how to improve workplace utilities services in UiTM Terengganu workplace. In the workplace, it is often assumed that office employees who are more satisfied with the physical environment are more likely to produce better work outcome. Therefore, this research will be a very useful tool for the organization in improving its services to its employees. This research is important in a way that it helps organization to know what contributes to the office employees’ satisfaction and it also helps the organization to focus on maintenance and renovation to those areas of deficiency. This research is a correlation research as it was conducted to investigate employees’ satisfaction towards workplace utilities. The population of this study refers to the office employees who are currently working in various departments in UiTM Terengganu, Dungun Campus. The total number of population for this study is 330. A simple random sampling technique will be used to choose the respondents from all departments. The questionnaire will be issued. The data obtained from the study will be analyzed by using the SPSS which tests the frequency distributions and Pearson Correlation.